PHARMACOLOGY OF PHTHALYLSULFACETAMIDE ACUTE TOXICITY AND DISTRIBUTION - TELLEZ GARCIA, DOLORES; PARDO, EFRAIN G; HIDALGO CHAVEZ, CONSUELO (Hospital General, CD MEXICO, DF, MEX, 1941)
Diurnal variations of renal function were studied by means of a constant infusion technic in 10 subjects with congestive heart failure In contrast to normal subjects, urine flow, Na excretion and filtration rate increased during sleep in 6 patients with
CIENC MEX
Keywords: PHARMACOLOGY, PHTHALYL SULFACETAMIDE, ACUTE TOXICITY, DISTRIBUTION; MULTIDISCIPLINARIA; FARMACOLOGIA; ANALISIS DE MEDICAMENTOS